Sustainable Urban Development Strategies for Slum Upgrading and Environmental Improvement using Material Science Technology - Kishan, A. Bala; Ali, Mohd Akhter; Kamraju, M. (ASEAN Journal for Science and Engineering in Materials, 2022)
This research paper explores sustainable urban development strategies aimed at upgrading slums and improving the environmental conditions within these settlements. Slums, characterized by substandard housing, inadequate access to basic services, and environmental degradation, pose significant challenges to urban areas worldwide. This study examines various approaches and interventions that promote sustainable development, focusing on slum upgrading and environmental improvement. By analyzing successful case studies, policy frameworks, and best practices, this research aims to identify effective strategies for creating inclusive, resilient, and environmentally sustainable urban communities.